Impact of ClO2 pre-oxidation on the formation of CX3R-type DBPs from tyrosine-based amino acid precursors during chlorination and chloramination. (April 2018) - Yao, Dechang; Chu, Wenhai; Bond, Tom; Ding, Shunke; Chen, Shenghua
Abstract: ClO2 is frequently used as a pre-oxidant in water treatment plants. However, the effects of ClO2 pre-oxidation on disinfection by-product (DBP) formation, especially the highly toxic nitrogenous DBPs, during subsequent chlor (am)ination have not been studied thoroughly. There is also limited information about DBP formation from combined amino acids (AAs), which are more abundant than free AAs in source waters. Many typical DBPs (including representative N-DBPs) have a similar structure of "CX3 R" (X = H, Cl, Br or I). In the study, tyrosine and forms representing its reactivity in combined AAs (tyrosine tert -butyl ester and Boc-tyrosine) were selected as model precursors. The formation of various regulated and unregulated CX3 R-type DBPs from ClO2 pre-oxidation and subsequent chlor (am)ination were studied at a wide-range of ClO2 and chlor (am)ine doses (ClO2 /precursors and chlor (am)ine/precursors are at the range of 0–2.5 and 1–20 [Mol/Mol], respectively). Chloroform and chloral hydrate (CH) yields increased with chlorine dose, while haloacetonitrile and haloacetamide maximized at median chlorine dose (Cl2 /Precursors = 10). All DBP yields increased with chloramine dose. ClO2 pre-oxidation increased chloroform, haloacetonitrile, trichloronitromethane and CH yields during chlorination, but ClO2 increased chloroform, CH, trichloroacetamide while decreased dichloroacetonitrile and trichloronitromethane yields during chloramination. The overall toxicity of the formed DBPs was evaluated by cytotoxicity index (CTI). ClO2 pre-oxidation increased CTI from all precursors during post-chlorination while reduced it during post-chloramination. Results imply that ClO2 is probably more suitable for use in combination with chloramination disinfection, rather than chlorination, in the integrated control of CX3 R-type DBPs from source waters abundant in AAs. Graphical abstract: Image 1 Highlights: ClO2 pre-oxidation increased CF and CH during chlor (am)ination of tyrosine-based amino acids. During chlorination, introduction of ClO2 increased HANs, TCNM and TCAcAm. During chloramination, introduction of ClO2 decreased DCAN and TCNM. CTI during chlorination were higher than that during chloramination. ClO2 pre-oxidation increased CTI in chlorination but reduced it in chloramination.